Sinusoidal growth, recruitment, mortality, yield-per-recruit analysis of Buried fan scallop Mimachlamys funebris (Reeve, 1853) and their implications for mariculture - Ian Cris R. Buban; Christian D. Cabiles; Renan U. Bobiles; Alex P. Camaya; Victor S. Soliman (Journal of Fisheries, 2020)
This study described the growth, mortality, recruitment pattern and exploitation rate of the Buried fan scallop (Mimachlamys funebris) in Asid Gulf, Philippines. Monthly length-frequency data (N=3988) from April 2018 to March 2019 were used to examine population parameters using FISAT II. Two estimates of natural mortalities were used to compare variability of limit exploitation rates. Modelling through the oscillating von Bertalanffy growth function revealed that the species is fast growing (K=1.1 year–1) attaining SH∞ of 10.5 cm. Adequacy in the use of the sinusoidal version of the growth formula hinges on the mean annual temperature difference reported in the gulf to be 2°C. Recruitment pattern was continuous and bimodal throughout the year with two high pulses in April–May and September consistent with the reproductive seasonality reported for congeneric species. Fishing mortality coefficients (4.26 and 4.82 year–1) were higher than the natural mortality coefficients (0.543 and 1.1 year–1). Yield and biomass-per-recruit analysis showed that the current exploitation rates are 112% (Ecurr1 = 0.90) and 92% (Ecurr2 = 0.80) higher than the biological reference points adopted for the study particularly E50. These results demonstrate that M. funebris stock is overexploited, which necessitates effective management measures including mariculture.